2007
DOI: 10.1016/j.ijpara.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The amastigote forms of Leishmania are experts at exploiting host cell processes to establish infection and persist

Abstract: Leishmania are dimorphic protozoan parasites that live as flagellated forms in the gut of their sandfly vector and as aflagellated forms in their mammalian hosts. Although both parasite forms can infect macrophages and dendritic cells, they elicit distinct responses from mammalian cells. Amastigotes are the parasites forms that persist in the infected host; they infect cells recruited to lesions and disseminate the infection to secondary sites. In this review I discuss studies that have investigated the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 91 publications
(91 reference statements)
1
92
0
15
Order By: Relevance
“…It is well established that internalization of amastigotes via phospatidylserine receptors on macrophages induces secretion of IL-10 and TGF-b, which in turn blocks induction of iNOS, resulting in decreased production of NO (5). Studies in the classical hamster model of VL also showed decreased expression of iNOS mRNA, accounting for defective parasite elimination, thereby enhancing disease progression (47).…”
Section: Parasitized Macrophages Had Decreased Levels Of No That Was mentioning
confidence: 99%
“…It is well established that internalization of amastigotes via phospatidylserine receptors on macrophages induces secretion of IL-10 and TGF-b, which in turn blocks induction of iNOS, resulting in decreased production of NO (5). Studies in the classical hamster model of VL also showed decreased expression of iNOS mRNA, accounting for defective parasite elimination, thereby enhancing disease progression (47).…”
Section: Parasitized Macrophages Had Decreased Levels Of No That Was mentioning
confidence: 99%
“…In fact an important mechanism through which TGF-b suppresses effector T cells is the promotion of regulatory T cells (Tregs) maintenance and differentiation [3,4]. TGF-b was shown to be involved in the expansion of both native and induced Foxp3 þ Tregs in malaria [5e7], toxoplasmosis [8], and leishmaniasis [9]. Both TCR-dependent and independent mechanisms have been demonstrated to account for Treg expansion during parasitic infections [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been conducted to examine how Leishmania promastigotes (the insect stage of the parasite) and amastigotes (the intracellular form) infect target cells and suppress the intracellular signaling events in macrophages [reviewed by (Kima, 2007) and ]. However, limited information is available regarding the molecular details as to how DCs respond to the intracellular amastigotes.…”
Section: Introductionmentioning
confidence: 99%